1991
DOI: 10.1038/eye.1991.22
|View full text |Cite
|
Sign up to set email alerts
|

Reducing disinfectant wastage

Abstract: SummaryIn order to lower departmental costs in an ophthalmological outpatient department by reducing wastage, the stability of available chlorine at levels of 280 ppm and 560 ppm in litre solutions of sodium dichloroisocyanurate was investigated over a three-week period. There was no significant decay in available chlorine at these levels in solutions kept at 20°C. Sodium dichloroisocyanurate may be prepared on a weekly instead of a daily basis with an annual saving of £1200 to £1400.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…Jang et al, (Jang et al, 2017) demonstrated that 0.3% SDIC solution possessed strong bactericidal efficacy against Salmonella enterica serovar Thyphimurium even for 1 min treatment at -10°C, whereas, 0.1% glutaraldehyde worked for 10 min treatment at 25°C. Since many experimental researches have indicated its increased resistance to inactivation by organic material, slow decomposition and release of HOCl, capacity to maintain an appropriate level of available chlorine, low level of toxicity and lower corrosiveness to metal, plastic and rubber (Block, 2001;Bloomfield and Miles, 1979;Coates, 1966;Kaye et al, 1991) , the use of SDIC instead of NaClO has been recommended. However, there have been few reports to investigate the effectiveness of SDIC as a disinfectant to dental field (Heling et al, 2001;Patel et al, 2012) .…”
Section: Introductionmentioning
confidence: 99%
“…Jang et al, (Jang et al, 2017) demonstrated that 0.3% SDIC solution possessed strong bactericidal efficacy against Salmonella enterica serovar Thyphimurium even for 1 min treatment at -10°C, whereas, 0.1% glutaraldehyde worked for 10 min treatment at 25°C. Since many experimental researches have indicated its increased resistance to inactivation by organic material, slow decomposition and release of HOCl, capacity to maintain an appropriate level of available chlorine, low level of toxicity and lower corrosiveness to metal, plastic and rubber (Block, 2001;Bloomfield and Miles, 1979;Coates, 1966;Kaye et al, 1991) , the use of SDIC instead of NaClO has been recommended. However, there have been few reports to investigate the effectiveness of SDIC as a disinfectant to dental field (Heling et al, 2001;Patel et al, 2012) .…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, a huge amount of papers has reported the higher efficacy of NaDCC with respect to NaOCl against a wide range of microorganisms, such as Gram-positive and Gram-negative bacteria as well as fungi and viruses that, in many cases, are relevant to hospital settings [2][3][4][5][6]14]. Many experimental results have recommended NaDCC instead of NaOCl for its biocidal effectiveness, such as its: increased resistance to inactivation by organic material, slow decomposition and release of HOCl, capacity to maintain an appropriate level of available chlorine without affecting the pH of the water, low level of toxicity and lower corrosiveness to metal, plastic and rubber [2,3,6,13].…”
Section: Introductionmentioning
confidence: 99%